2011
DOI: 10.1007/s11302-011-9218-y
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial P2X7 receptor current density increased following long-term exposure to rotenone

Abstract: The role of the interaction between neurons and glial cells in the pathogenesis of neurodegenerative diseases is gaining more attention. Neuroinflammation participates in the progressive nature of diverse neurologic diseases including Parkinson's disease, Alzheimer's disease and multiple sclerosis. Activated microglia release neurotoxic molecules, which take part in the neuroinflammatory responses. Astrocytes are also key players in these responses. Reactive astrocytes secrete inflammatory factors, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Astrocytes were harvested from neonatal rats (P2‐3) as previously described . The mixed cells were plated onto PLL‐coated culture flasks and incubated in DMEM (Gibco, Grand Island, NY, USA) containing 10% FBS (Sigma).…”
Section: Meterials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes were harvested from neonatal rats (P2‐3) as previously described . The mixed cells were plated onto PLL‐coated culture flasks and incubated in DMEM (Gibco, Grand Island, NY, USA) containing 10% FBS (Sigma).…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…Twelve hours after treatments, the astrogliosis was examined by measuring GFAP fluorescence intensity as described previously . Briefly, astrocytes were fixed with 4% paraformaldehyde in PBS for 20 min, washed with 0.1 M PBS (pH 7.4), and then incubated overnight at 4°C with rabbit‐anti‐GFAP primary antibody (1:200; Abcam).…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…In PD, as in the case of AD, neuroinflammation also plays a crucial role in development of this disorder. Microglial cells are chronically stimulated by substances released from dead neurons and activated astrocytes, including extracellular nucleotides [ 124 ]. Released ATP may act as a factor accelerating the progression of the PD caused by genetic or environmental factors [ 58 ].…”
Section: Selected Conditions Of the Nervous Systemmentioning
confidence: 99%
“…Released ATP may act as a factor accelerating the progression of the PD caused by genetic or environmental factors [ 58 ]. Activated microglia of the substantia nigra releases ROS and cytokines such as IL-1β, IL-6 and TNF-α, which during the initial stage may play the protective role towards neurons, however, as the disease progresses, these may become neurotoxic and may exacerbate the neurodegeneration [ 124 , 125 ]. The following was noted in dopaminergic nigrostriatal region and in cerebrospinal fluid of PD patients: (1) increased level of proinflammatory cytokines such as IL-1β, IL-2, IL-4, IL-6 and TNF-α; (2) increased level of factors associated with apoptosis, including TNF-α receptor R1 (p55), soluble Fas, Bcl-2 and elevated caspase-1 and caspase-3 activities; (3) lowered level of neurotrophins, such as BDNF and NGF (nerve growth factor) [ 126 ].…”
Section: Selected Conditions Of the Nervous Systemmentioning
confidence: 99%
“…Furthermore, a different approach using intragastrically administered rotenone (5 mg/Kg) in mice showed that the accumulation and aggregation of α-synuclein in neurons of the dorsal motor nucleus of the vagus (DMV) and the intermediolateral nucleus (IML) in the spinal cord was accompanied by the selective loss of dopaminergic neurons and astrogliosis, suggesting that the gastric administration of rotenone through the connection of the enteric nervous system (ENS) with anatomical structures of the CNS also induces PD-like features [11,19]. Rotenone has also been shown to cause increased expression of connexin43 (Cx43), which forms gap junctions, and P2X7 receptors that modulate cytokine secretion and gamma tubulin; these are important for the adequate function of the cytoskeleton and organelles such as the Golgi apparatus [70][71][72][73]. Moreover, rotenone induces astrogliosis and alterations in the expression of g-tubulin, signal transducer and activator of transcription 3 (STAT3), and connexin 43 in astrocytes [70,72,74].…”
Section: Rotenone As a Parkinson Modelmentioning
confidence: 99%